Bridging the gap: the role of 3D cell cultures in mimicking tumor microenvironment for enhanced drug testing accuracy - Zhou, Yan; Yu, Feiyuan; Guo, Min; Tang, Yao; Xu, Qian (Frontiers in Bioengineering and Biotechnology, 2025)
Cell culture is a crucial technology in life science research, particularly in cancer studies. The morphology and biological properties of tumor cells, along with the mechanisms of tumor development, are highly dependent on their culture conditions. Antitumor drug sensitivity testing is essential for cancer treatment, helping to identify effective therapies and reduce patient treatment burden. Currently, 2D cell culture remains the primary method for antitumor drug sensitivity testing due to its cost-effectiveness, ease of operation, and high-throughput screening capability. However, it does not accurately replicate the tumor microenvironment. Animal models are important tools for drug development, but they are not suitable for high-throughput screening. Recent advancements in 3D culture technologies have addressed this limitation. These technologies can better mimic the tumor microenvironment and can accurately reflect tumor biological behavior, gene expression, and signaling pathways. This paper summarizes the current in vitro and in vivo culture models, discusses emerging three-dimensional cell culture technologies, and highlights their ability to effectively simulate the tumor microenvironment and their significant potential in drug sensitivity testing.